Analisis Pengaruh Modifikasi Pressure Reducing Valve Terhadap Range Pressure Drop Aliran Uap - Anwar, Kelly; Gunawan, Harjadi; Tobing, Sheila (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2024)
Pressure Reducing Valve (PRV) is a control valve designed to reduce upstream pressure to downstream pressure on fluid flow. When operating, a PRV is in an equilibrium condition because of the forces acting on it, such as fluid resultant force, membrane force, and spring force. On some working conditions, a PRV cannot operate because the equilibrium is unattainable by the spring that deflects further than the maximum allowable limit and unable to produce force balancing out other forces. Therefore, a modification on the spring wire diameter from 17 mm to 20 mm is conducted without altering other PRV parts dimension and geometry. The modified spring will be analysed through analytical analysis and simulation analysis with Ansys software. On the same working conditions with the enlargement of the spring wire diameter, the deflection that once was 99,28 mm decreases to 42,64 mm and does not exceed the maximum limit at 74,375 mm so the PRV can operate on said condition and the pressure drop range increases from 7 bar to 9 bar.